Regulation Of Web-Based Entertainment In India: Evaluating Self-Regulation Over Censorship As A Mechanism For Regulating Ott Platforms (Journal of Namibian Studies : History Politics Culture, 2023)
This article attempts to study the recent debate over censorship of entertainment content produced and disseminated over several Over-the-Top (OTT) Platforms so as establish a parity between regulation of theatrical cinema and entertainment content over these platforms. The prime objective of this study is to analyse the difference between Certification and Censorship of Films so as to justify the demand for Self-Regulation by various OTT platforms. Further, the study proposes recognition of Right to say No and Right of Choice as social freedoms in the context of nature of entertainment content is sought to be viewed by the consumers. This shall further the peaceful exercise of right to free speech and expression of producers of content and every such OTT platform where such content is broadcast. With the Government releasing “The Information Technology (Intermediary Guidelines and Digital Media Code of Ethics) Rules 2021”, several questions pertaining to self-regulation of OTT platforms have emerged. This research discusses if censorship of OTT platforms may curtail their right to free speech and expression, and therefore evaluates the need for self-regulation over the former as a method of grading the nature, quality and appropriability of content available over these platforms. The research concludes that the censorship is a misnomer and cannot be applied to OTT platforms as the nature of content between cinema and web-based entertainment is completely different. This is the result of India gradually becoming an ‘experience economy’ where the viewer’s choices and web-based entertainment content have garnered a much wider demand than theatrical cinema.